The Effectiveness of Problem-Based Learning Models in Improving Students’ Critical Thinking Skills - Abelia Berliana Casandra; Haikal Novendra Alfanzani; Vera Hamidah (Indonesian Journal of Educational Innovation, 2025)
In the 21st century, enhancing students’ critical thinking skills is crucial for developing highquality human resources. In physics education, students often struggle to analyze problems, apply concepts, and draw logical conclusions, indicating a limited ability to think critically. This issue is often associated with teacher-centered learning methods. This study investigates the effectiveness of the Problem-Based Learning (PBL) model in enhancing students’ critical thinking skills in the context of static fluids. Using a quasi-experimental design, 72 grade XI science students were divided into control and experimental groups. The experimental group received PBL instruction, while the control group followed traditional methods. Data from pre-tests and posttests were analyzed using independent sample t-tests. Results showed that the experimental group had significantly higher critical thinking scores. This finding suggests that PBL effectively fosters students’ critical thinking by encouraging inquiry, collaboration, and real-world problem solving